Research of microenterprises in Latvia in the context of resolving unemployment - Павук, Ольга (Technology audit and production reserves, 2014)
Based on the data of the Register of Enterprises of the Republic of Latvia, the State Revenue Service, Report on the Development of the National Economy of Latvia and publications in periodicals, the author examines the place and role of microbusiness on the labor market of Latvia. According to Eurostat, in mid-2014 the unemployment rate in Latvia was by 11.4% higher than in neighboring Estonia and Lithuania. And this despite the deterioration of the demographic situation and the continuing outflow of economically active population to Western countries. Over the past 10 years, the population of Latvia has decreased by 13%, from 2.319 million people in 2004 to 1,995 million people in mid-2014. Microenterprises started to be established in Latvia in 2010 in the midst of the economic crisis as one of the measures to overcome unemployment, which exceeded 20%. Today, the share of microenterprises is 85.5% of all enterprises. Herewith, the turnover of all the microenterprises is 1% of the total turnover of all enterprises in the country. Mass registration of microenterprises with the facilitated taxation has led to a reduction in unemployment. However, not having got the expected effect of the tax collection from microenterprises, fiscal authorities have decided to increase the turnover tax from 9 to 15% for them starting from 2015. This decision has led to a sharp reduction in the registration of new microenterprises in the current year and, thus, to an increase in unemployment. According to the author, in view of the Latvia’s economy structure, it is necessary to create conditions for the more efficient activity of microenterprises and bringing them out of the shadows, for which the turnover tax should be reduced rather than increased. The question of increasing the turnover tax can be placed after the microenterprises will operate at a profit.